If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + 4y = -8 Solving 10x + 4y = -8 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4y' to each side of the equation. 10x + 4y + -4y = -8 + -4y Combine like terms: 4y + -4y = 0 10x + 0 = -8 + -4y 10x = -8 + -4y Divide each side by '10'. x = -0.8 + -0.4y Simplifying x = -0.8 + -0.4y
| 2x-12x=6 | | u^2-2u+32=(2u-5)(u+2) | | 3x^10=3 | | 5(3x-2)+34x-7=24x-8 | | -7(7-3x)=-4(10-6x) | | 7a^2=19-8a | | x^2+.7x+.1=0 | | 8s(s+4)=s-21 | | 4(7-2b)+2(5b+2)= | | -0.2x-0.3y=0.2 | | -x+5-3x=-55 | | 5x-35=x-13 | | 10x=15x-15 | | 8x-6=5x-12 | | 2(23-x-2y)+2(23-x-7)=20 | | 4(x+3)=3x+3 | | 2(x+2)=3x-4 | | 2v+4=-2(2v+4) | | -6-7(5k-7)=3k-11(1+4k) | | 0=2x^3+8x+1 | | y=392-47.5x | | (-2*-2*-2*-2)-3(6+7)= | | 10=2x+8x | | 2+5r=26 | | 3n+24= | | x+y+2z=23 | | -1+x=x+11 | | x+6=1+2x+8 | | 0.16(y-8)+0.10y=0.18y-0.09(10) | | 11(-7n+4)=-23-11n | | 1.5k+3.5=-4 | | -3x-24=-6x+33 |